Comparative study of printed circuit board recycling by cracking of internal layers using organic solvents-dimethylformamide and dimethylacetamide - Verma H.R.; Singh K.K.; Mankhand T.R. (My University, 2025)
Dissolution studies of the substrate resin of waste printed circuit boards (WPCBs) in two organic solvents have shown that dimethylacetamide (DMAc) is more effective than dimethylformamide (DMF). Variation of dissolution parameters elucidated that DMAc results in 20% more resin dissolution when the temperature is increasing from 120 °C to 140 °C. It also results in 217% higher dissolution efficiency when the WPCBs:DMAc (w/v) ratio is increased to 3:10 from 1:10. The DMAc showed higher dissolution of the resin than DMF, for WPCBs of different size under conditions viz.- 140 °C, and 3:10 (w/v) WPCB:solvent ratio. The WPCBs of 2.25 cm2 size were completely separated into glass fiber matrix and copper foils in 180 min. Dissolution of resin is associated with the hydrogen bonding interaction with parent DMAc molecule. Spent DMAc has been regenerated by rotary decompression evaporator and it's chemical structure and boiling point were found similar to pure DMAc. Dissolved solute in the DMAc has been recovered as the residue during regeneration. The residue and exhibits a thermal degradation profile and chemical structure similar to untreated brominated epoxy resin. © 2016 Elsevier Ltd